2016
DOI: 10.1101/082651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-risk human papillomavirus in oral cavity squamous cell carcinoma

Abstract: 21Purpose: The prevalence of human papillomavirus (HPV) in oral cavity squamous cell carcinoma 22 (OSCC) varies significantly based on assay sensitivity and patient geography. Accurate detection is 23 essential to understand the role of HPV in disease prognosis and management of patients with 24 OSCC. 25Methods: We generated and integrated data from multiple analytes (HPV DNA, HPV RNA, and 26 p16), assays (immunohistochemistry, PCR, qPCR and digital PCR) and molecular changes (somatic 27 mutations and DNA meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…[ 17 ] and Palve et al . [ 18 ] detected the presence of E6 transcript by SYBR Green-based qPCR assay. On the other hand, the transcripts E6/E7 were detected by consensus PCR in the study conducted by Shima et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] and Palve et al . [ 18 ] detected the presence of E6 transcript by SYBR Green-based qPCR assay. On the other hand, the transcripts E6/E7 were detected by consensus PCR in the study conducted by Shima et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Thus, mRNA profiling can be performed along with the detection of DNA for early and confirmatory detection of HPV infection. [ 18 26 ] However, its use as a biomarker in the diagnosis of OSCC is contradictory due to its instability as compared to DNA and protein. RNA can also be silenced by host defense mechanism and hence may not lead to the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, two of the DNA-positive samples did not show HPV16 viral transcripts. Correspondingly, a study by Palve et al [50] demonstrated that only 15% of tumors that were HPV DNApositive had E6/E7 mRNA expressed. This could mirror a transient infection irrelevant to carcinogenesis [41,42,51].…”
Section: Discussionmentioning
confidence: 94%